2006
DOI: 10.1111/j.1440-1819.2006.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact among the public of the severe acute respiratory syndrome epidemic in Taiwan

Abstract: During the 2003 outbreak, severe acute respiratory syndrome (SARS) spread to more than 30 countries. Not only did it cause severe health problems but it also imposed a great psychological impact on the public. SARS emerged in Taiwan during April 2003. This study investigates the psychosocial impact and the associated factors of depression of the SARS epidemic in Taiwan when the epidemic had just been controlled. A total of 1552 respondents were recruited in the study by random selection from the telephone book… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
193
1
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(220 citation statements)
references
References 12 publications
13
193
1
13
Order By: Relevance
“…This study firstly found that the prevalence of PTSS a month after the COVID-19 epidemic for hardest-hit areas in China was 7%. Compared with a previous study (Ko et al, 2006), which reported a prevalence of 3.7% of depression symptoms during the post-SARS epidemic for an extrapolated target population in Taiwan. This psychiatrically outbreak seems to have an even greater impact on the public.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This study firstly found that the prevalence of PTSS a month after the COVID-19 epidemic for hardest-hit areas in China was 7%. Compared with a previous study (Ko et al, 2006), which reported a prevalence of 3.7% of depression symptoms during the post-SARS epidemic for an extrapolated target population in Taiwan. This psychiatrically outbreak seems to have an even greater impact on the public.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have explored the psychological effect during such epidemics, such as Severe Acute Respiratory Syndrome (SARS) and H1N1. One study reported that 3.7% of public cases, including 9.6% of "impacted group" (they or their friends and family had been quarantined, or suspected of being infected), had experienced depression symptoms since the SARS outbreak (Ko, Yen, Yen, & Yang, 2006). Another study showed 17.3% significant mental symptoms among health care workers during SARS epidemic (Lu, Shu, Chang, & Lung, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After the health emergencies, such as Severe Acute Respiratory Syndrome (SARS) epidemic in 2003, the Ebola outbreak in 2014, the Middle East Respiratory Syndrome (MERS) period in 2015 and so on, psychological problems were reported, such as fear, boredom, anxiety and depression [8][9][10][11]. And several studies reported that taking effective psychological intervention was essential to improve the mental health of the population after the epidemic [12,13]. Research observed that for dialysis patients, 38.1% of them had symptoms including anxiety and depression and 57.1% presented stress [14] even under normal circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Such negative community responses might cause individual and societal harm, as witnessed during the epidemic of severe acute respiratory syndrome ( 6 ). Misconceptions concerning transmission modes were prevalent and significantly correlated with both dependent variables.…”
mentioning
confidence: 99%